Sex-Biased Mortality and Sex Reversal Shape Wild Frog Sex Ratios - Lambert, Max R.; Ezaz, Tariq; Skelly, David K. (Frontiers in Ecology and Evolution, 2021)
Population sex ratio is a key demographic factor that influences population dynamics and persistence. Sex ratios can vary across ontogeny from embryogenesis to death and yet the conditions that shape changes in sex ratio across ontogeny are poorly understood. Here, we address this issue in amphibians, a clade for which sex ratios are generally understudied in wild populations. Ontogenetic sex ratio variation in amphibians is additionally complicated by the ability of individual tadpoles to develop a phenotypic (gonadal) sex opposite their genotypic sex. Because of sex reversal, the genotypic and phenotypic sex ratios of entire cohorts and populations may also contrast. Understanding proximate mechanisms underlying phenotypic sex ratio variation in amphibians is important given the role they play in population biology research and as model species in eco-toxicological research addressing toxicant impacts on sex ratios. While researchers have presumed that departures from a 50:50 sex ratio are due to sex reversal, sex-biased mortality is an alternative explanation that deserves consideration. Here, we use a molecular sexing approach to track genotypic sex ratio changes from egg mass to metamorphosis in two independent green frog (Rana clamitans) populations by assessing the genotypic sex ratios of multiple developmental stages at each breeding pond. Our findings strongly imply that genotypic sex-biased mortality during tadpole development affects phenotypic sex ratio variation at metamorphosis. We also identified sex reversal in metamorphosing cohorts. However, sex reversal plays a relatively minor and inconsistent role in shaping phenotypic sex ratios in across the populations we studied. Although we found that sex-biased mortality influences sex ratios within a population, our study cannot say at this time whether sex-biased mortality is responsible for sex ratio variation across populations. Our results illustrate how multiple processes shape sex ratio variation in wild populations and the value of testing assumptions underlying how we understand sex in wild animal populations.